(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
Abstract The present article shows the opinion of Principals and theses on some factors of the work dynamics, which is generated in the elaboration of the final graduation work (FGW), of the Degree in the Teaching of Sciences, where each Principal with his thesis students forms a virtual team. The projects or FGW of this program pretend to be a solution to problems that correspond to the internal or external community of an educational institution, for the improvement of scientific education.